On high-order model regularization for multiobjective optimization. (2nd January 2022) - Calderón, L.; Diniz-Ehrhardt, M. A.; Martínez, J. M.
Abstract : A p -order regularization method for finding weak stationary points of multiobjective optimization problems with constraints is introduced. Under Hölder conditions on the derivatives of the objective functions, complexity results are obtained that generalize properties recently proved for scalar optimization.